Innovative Pedagogical Strategies And The Use Of Information Technologies In Teaching Foreign Languages For Students Of Economic Specialties - Sadriddinova Dildora Muhammadjonovna (Euro Asian Journal Publishing, 2024)
This article examines the integration of innovative pedagogical strategies and information technologies in the teaching of foreign languages for students of economic specialties. The purpose of the study is to assess the impact of these approaches on language skills, intercultural competence and learning motivation of students. In addition, the article examines the use of authentic materials and effective assessment and feedback methods that contribute to a deeper understanding and application of the language. The author argues that the introduction of innovative pedagogical strategies and information technologies prepares students of economic specialties for successful functioning in the global business world.
Keywords: innovative pedagogical strategies; information technologies; teaching foreign languages; students of economic specialties